DIGITAL ASSESSMENT PRACTICES IN ISLAMIC RELIGIOUS EDUCATION: EVIDENCE FROM THE MY ALAZKA PLATFORM IN AN INDONESIAN ISLAMIC PRIMARY SCHOOL - Naila Nafahatus Sahariyah Al-Ulya; Is’ad Churiyah Zahidah; Muhammad Fikri Fardiyansyah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2026)
The digital transformation of Islamic schools demands new methods of assessing learning outcomes that are fast, transparent, and grounded in spiritual values. SD Islam Al Azhar Kelapa Gading Surabaya utilizes the My Alazka platform to manage Islamic Religious Education assessments online. This study focuses on how the system is implemented and its impact on teachers and students A qualitative case-study approach was employed through interviews, observations, and documentation, with data analyzed using the interactive model of Miles, Huberman, and Saldaña involving data reduction, data display, and conclusion drawing. The findings reveal that the use of My Alazka simplifies test management, accelerates grading, and presents learning results in real time. Teachers act as digital murabbīs, instilling honesty, responsibility, and justice throughout the assessment process. Students feel more motivated as they can immediately view their progress through an interactive digital interface. Overall, the implementation of My Alazka demonstrates an effective integration between technological efficiency and Islamic values such as amanah (trustworthiness), ‘adl (justice), and ihsan (excellence) in PAI learning within the digital era.